Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/jp2052344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Highly Exfoliated and Oriented Organoclays on the Barrier Properties of Polyamide 6 Based Nanocomposites

Abstract: The influence of the incorporation of nanoparticles (organo-modified montmorillonite Cloisite 30B) in polyamide 6 (PA6) on the transport of small molecules was investigated. Nanocomposites were prepared by melt blending followed by cast extrusion for obtaining film-forming materials. The nanoclay content of the materials was varied from 0 to 5 vol%. Differential scanning calorimetry measurements, electronic microscopy, X-ray diffraction, and rheology were used for characterizing the nanocomposite structure. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 68 publications
3
49
0
1
Order By: Relevance
“…Of the studies reviewed in Table 1, some have measured the aspect ratio using transmission electron microscopy (TEM) [16,50,51,56] whereas others have calculated the value from fitting experimental data to one of the models [33,50,51,54,56,66]. Comparing the studies where aspect ratios have been measured, modest values (of 20, 38 and 52) were reported for samples prepared by melt processing.…”
Section: Aspect Ratio and Filler Concentrationmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the studies reviewed in Table 1, some have measured the aspect ratio using transmission electron microscopy (TEM) [16,50,51,56] whereas others have calculated the value from fitting experimental data to one of the models [33,50,51,54,56,66]. Comparing the studies where aspect ratios have been measured, modest values (of 20, 38 and 52) were reported for samples prepared by melt processing.…”
Section: Aspect Ratio and Filler Concentrationmentioning
confidence: 99%
“…Bharadwaj [22] can be successfully applied [50,56,62]. Other models are claimed to be more suitable for predicting behaviour at high filler aspect ratios.…”
Section: Review Of Model Validationmentioning
confidence: 99%
See 3 more Smart Citations